Temperature dependence of polaron stability in conjugated polymers. (29th July 2015) - Zhang, Y. L.; Liu, X. J.; An, Z.
Abstract: Within a tight-binding electron-phonon interaction model modified to include thermal effects, the theoretical temperature dependence of polaron stability in conjugated polymers is investigated using a nonadiabatic evolution method. It was found that temperature effects lead to polaron states becoming delocalized, while many weakly localized polaron states are generated. It is worth noting that after thermal equilibrium of the system has been reached, energy transfer between the lattice and the electrons still slowly takes place through two different physical processes corresponding to lower and higher temperatures.